Erosion hazard mapping and land use strategy in Sempor Reservoir Watershed of Central Java, Indonesia - Pancarani, Anggun Melia; Adipradana, Arrizka Yanuar; Amin, Muhammad (Brawijaya University, 2025)
Land use change is a significant factor in accelerating erosion rates, which is expected to increase sedimentation in the reservoir. The reduction in the water storage capacity of the dam is primarily due to sediment accumulation resulting from soil erosion. One of the approaches involves analyzing the erosion hazard level by integrating the Geographical Information System (GIS) and the Soil and Water Assessment Tool (SWAT) to accurately predict the erosion rate. The objective of this research was to assess the erosion hazard level and develop land management strategies to mitigate erosion rates in Sempor Reservoir Watershed of Central Java, Indonesia. The SWAT model employed the Modified Universal Soil Loss Equation (MUSLE) method, utilizing input data on topography, climatology, and land use provided by an authorized agency. Model calibration was conducted using the Calibration Uncertainty Program, which involved 55 iterations with 2,000 simulations per iteration, incorporating 18 sensitive parameters. Furthermore, the comparison of flow discharge between observed and simulated data is validated using statistical parameters. The results indicated that land use coverage and slope significantly influence the erosion rate. The land management strategy scenario demonstrates a reduction in potential erosion rates and sediment yield. Model calibration and validation yielded R² values of 0.87, NSE of 0.86, and PBIAS of 3.6%, indicating an excellent model fit. This suggests that the SWAT model is quite accurate in simulating the catchment area. However, the SWAT model's performance can be further enhanced by improving the adaptability of other calibration parameters.